PEMETAAN PEMASARAN KERELASIAN PELANGGAN, KOLABORASI PEMASOK, SUMBER DAYA PERUSAHAAN, KEUNGGULAN BERSAING DAN KINERJA PEMASARAN - hamzah, hamir (Jurnal Sains dan Teknologi Indonesia, 2011)
To find out the cause of poor performance of SMEs metal automotive components in Java, author mapping “Customer Relationship Marketing, Suppliers Collaboration, Firm Resources, Competitive Advantage, Performance Marketing (a survey of SMEs metal automotive components in Java). "This study used 221 respondents SMEs metal automotive components in Java with cluster random sampling method and usingdescriptive analysis for qualitative variables. SMEs metal automotive components in the Java able to build relationship marketing with customers. The best form of customer Relationship marketing is the interaction of technical draw information, while the less good is the product creation process of technical assistance. SMEs metal automotive components are able to build collaboration with suppliers. The best form of suppliers collaboration is information of specification and amount of raw materials, while the less one is the raw material of knowledge transfer. Firm resources owned by SMEs metal automotive components in Java is strong enough. The resources of the most powerful companies are experienced human use of existing machinery and equipment, while theweakest are the royalty payments from its findings. SMEs metal utomotive components capable of creating competitive advantage. The best element of competitive advantage is able to achieve rapid delivery times, while that have not been able to achieve is to reduce the price of the product through increased labor productivity. SMEs metal automotive components, although able to improve marketing performance, but sales growth is still low and relatively small profit margins, and customer growth is still low.